Pemberdayaan Kepada Masyarakat Melalui Pengelolaan Sampah Berbasis 3R (Reduce, Rause, Recycle) di Desa Sukowono - Abdul Ghoni Hasanul Islam; Rini Puji Astuti; Ahmad Syarifudin Hidayat; Dahniar Ananda; Dwi Latifa Rizqina; Faiqqotul Hikmah; Istofina Azzaroh; Jonata Aldonama; Lukman Kholifatur Rahman; Maya Anggraini; Moh Samsul Rifa’i; Najwa Bariroh; Oscar Achmad Djunaedi; Rika Ifana Putri Mayangsari; Selfi Dwi Anggraini; Siti, Siti (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Waste management is an important issue that affects environmental quality and public health. In an effort to increase community awareness and participation in waste management, this research uses a Participatory Action Research (PAR) approach. Through the PAR method, the community is directly involved in every stage of planning, implementation, and evaluation of waste management programs. This approach aims to strengthen community participation in finding solutions that are sustainable and in accordance with local needs. Activities carried out include counseling, training, and the formation of waste management groups at the neighborhood level, with an approach based on existing local potential and wisdom. The results showed that the use of the PAR method succeeded in increasing community awareness about the importance of independent and sustainable waste management. Active participation of residents in waste management can reduce the volume of waste disposed to landfills and improve environmental quality. In addition, this program also creates a sense of belonging and shared responsibility in maintaining environmental cleanliness. Overall, community-based waste management has proven to be effective in creating behavioral changes that are more environmentally friendly and sustainable, as well as building social solidarity among residents.